TRADISI PETIK LAUT UMAT HINDU DAN ISLAM DI DESA PENGAMBENGAN KECAMATAN NEGARA KABUPATEN JEMBRANA - Ni Nyoman Sariyani (Jurnal Widya Sastra Pendidikan Agama Hindu, 2020)
This study was aimed to know: 1) The history of “Petik Laut” tradition at Pengambengan village, Negara district, Jembrana Regency; 2) The sequences of “petik Laut” tradition at Pengambengan village, Negara district, Jembrana regency; 3) The participation between Hindu and Muslim people in conducting “Petik Laut” tradition at Pengambengan village, Negara district, Jembrana regency; 4) The benefit and meaning of “Petik Laut” tradition at Pengambengan Village, Negara district, Jembrana regency. This study is a qualitative research. Purposive sampling technique was used in this study. The method of data collection in this study were observation, interview, and note taking. While descriptive comparative was used in this study for the data analysis. Based on the data analysis, there were findings that “Petik Laut” tradition was began by ancestors as a thanksgiving and gratefulness given to the Pengambengan people because of what they had while doing fishing. The sequences of “Petik Laut” tradition at Pengambengan village were done during three days; there are preparation, implementation, and closing. “Petik Laut” tradition were done by Hindu and Muslim people by using different means based on their own beliefs. The participation between Hindu and Muslim people in conducting “Petik laut” tradition were equal based on their rituals. By doing “Petik Laut” tradition, people at Pengambengan village belief that their haul will be increasing. There are several meanings of “Petik Laut” tradition, they are: instrumental meaning, teamwork meaning, religion meaning, Hindu religion meaning, tolerance meaning, and social interaction meaning.